Study of Heat-Recovery Systems for Heating and Moisturing Combustion Air of Boiler Units - Fialko, N.M.; Navrodska, R.O.; Gnedash, G.O.; Presich, G.O.; Shevchuk, S.I. (Наука та інновації, 2020)
Introduction. One of the ways to save natural gas and to improve the environmental conditions in the municipal
heat-power engineering is to use progressive technologies for recovering the heat of flue gases from boiler
plants, in which the condensation mode of operation of heat-recovery equipment is implemented. To increase
the ecological effect in some heat-recovery systems, a humidification process of the combustion air occur. This
lowers the combustion temperature of the fuel and reduces the concentration of nitrogen oxides in the combustion
products. Problem Statement. At humidifying combustion air, the boiler exhaust-gases are characterized by high moisture
content. In the known calculation methods, there are no data on heat transfer under these conditions. This is
a problem for conducting thermal calculations of such installations.
Purpose. Establishing patterns of heat transfer at an increased moisture content of exhaust-gases in heatrecovery
equipment, consisting of bundles of transverse-finned pipes, and determining the main parameters of
the proposed complex installation. Materials and Methods. Experimental studies of heat transfer were carried out on a specially created stand. For the thermal and hydraulic calculation of a heat-recovery installation, known calculation methods were used,
taking into account the experimental data obtained.
Results. The laws of heat transfer during deep cooling of exhaust-gases with moisture content X = 0.15—0.30
kg/kg d.g. are established. The thermal, hydraulic and operating characteristics of the proposed complex
heat-recovery installation with heating and humidification of the combustion air in different modes of operation
of the boiler are determined. This installation has been introduced; its tests have been carried out, which have
confirmed high thermal and environmental efficiency.
Conclusions. The application of the proposed complex heat-recovery unit allows increasing the coefficient
of the use heat of fuel of boiler depending on its operating mode by 13—20%. Вступ. Одним зі шляхів економії природного газу й поліпшення умов довкілля є застосування
в комунальній
енергетиці прогресивних технологій утилізації теплоти відхідних димових газів котельних установок, в яких реалізується
конденсаційний режим роботи теплоутилізаційного обладнання. Для підсилення екологічного ефекту в
деяких теплоутилізаційних системах відбувається процес зволоження дуттьового повітря, що зменшує температуру
горіння палива та знижує концентрацію оксидів азоту в продуктах згоряння.
Проблематика. При зволоженні дуттьового повітря відхідні гази котла характеризуються підвищеним вмістом
вологи. У відомих розрахункових методиках відсутні дані щодо теплообміну за цих умов. Це є проблемою для проведення
теплових розрахунків таких установок.
Мета. Встановлення закономірностей теплообміну при підвищеному вологовмісті димових газів в теплоутилізаційному
обладнанні, що складається з пучків поперечно оребрених труб, і визначення основних параметрів запропонованої
комплексної установки.
Матеріали й методи. Експериментальні дослідження теплообміну проводилися на спеціально створеному стенді.
Для теплового та гідравлічного розрахунку теплоутилізаційної установки застосовано відомі розрахункові методики
з урахуванням отриманих експериментальних даних.
Результати. Встановлено закономірності теплообміну при глибокому охолодженні димових газів із вологовмістом
Х = 0,15—0,30 кг/кг сухих газів. Визначено теплові, гідравлічні та режимні характеристики запропонованої
комплексної теплоутилізаційної установки з підігріванням і зволоженням дуттьового повітря в різних режимах
роботи котла. Розробку було впроваджено, проведено її випробування, які підтвердили високу теплову та екологічну
ефективність.
Висновки. Застосування запропонованої комплексної теплоутилізаційної установки дозволяє підвищити коефіцієнт
використання теплоти палива котла на 13—20 % залежно від режиму його роботи.